Building Intercultural Competence One "Patch" at a Time. (13th January 2013) - Spooner-Lane, Rebecca; Tangen, Donna; Mercer, K. Louise; Hepple, Erika; Carrington, Suzanne
Abstract : This paper describes a program called Patches that was implemented to assist a group of Australian and Malaysian pre-service teachers to enhance their intercultural competence through their involvement in a series of reciprocal learning activities. Each learning experience was considered a "patch" that eventually created a "quilt of intercultural learning." The purpose of this study was to enhance the intercultural competence of domestic and international students through organized intercultural activities, through a series of reflective writing sessions, and mutual engagement on a common project. The effectiveness of the Patches program was analysed in accordance with Deardorff's elements of intercultural competence. The qualitative findings indicate that both cohorts of preservice teachers showed elements of intercultural competence through participation in the program, with both groups reporting a deeper appreciation and understanding of how to communicate more effectively in intercultural contexts.